2020
DOI: 10.3390/md18030143
|View full text |Cite
|
Sign up to set email alerts
|

Micro RNA Expression after Ingestion of Fucoidan; A Clinical Study

Abstract: Fucoidans are a class of fucose-rich sulfated polysaccharides derived from brown macroalgae that exert a range of biological activities in vitro and in vivo. To generate an unbiased assessment of pathways and processes affected by fucoidan, a placebo-controlled double-blind pilot study was performed in healthy volunteers. Blood samples were taken immediately before and 24 h after ingestion of a single dose of 1 g of Undaria pinnatifida fucoidan (UPF) or placebo. Levels of isolated miRNAs were analyzed using Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
(41 reference statements)
0
13
0
1
Order By: Relevance
“…Natural products adapted for medicinal purposes can have powerful downstream health benefits in the human body. Gueven et al performed research using human subjects and showed that the oral administration of fucoidan from the brown (Phaeophyceae) macroalga Undaria pinnatifida affected the expression of 53 micro-RNAs in the hours and days following consumption [ 229 ]. These micro-RNAs have been implicated in diverse functions throughout the human body relating to immune function, cell growth and division, inflammation, and neurological control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural products adapted for medicinal purposes can have powerful downstream health benefits in the human body. Gueven et al performed research using human subjects and showed that the oral administration of fucoidan from the brown (Phaeophyceae) macroalga Undaria pinnatifida affected the expression of 53 micro-RNAs in the hours and days following consumption [ 229 ]. These micro-RNAs have been implicated in diverse functions throughout the human body relating to immune function, cell growth and division, inflammation, and neurological control.…”
Section: Discussionmentioning
confidence: 99%
“…6 ). Furthermore, early research has shown that consumption of algae modifies the profile of host gene expression with some potential benefits to immune response [ 229 ]. In Section 2.4 , we provide an overview of some important immune-activating properties observed in algae-derived compounds ( Table 11 , Fig.…”
Section: Viral Pathogenesismentioning
confidence: 99%
“…Since VEGF-A is well known to promote tumor progression [27], even a small effect is not desirable as an anticancer effect. However, an influence of fucoidans on the gene expression level is shown for commercially available fucoidan from Undaria pinnatifida (Marinova), which is able to change the gene expression of cancer-related and cell surface signaling-related pathways [28]. But this alga is from another brown algae order and was used in a clinical study with human blood serum, which could explain the differences.…”
Section: Discussionmentioning
confidence: 99%
“…Gueven et al [ 347 ] showed that a single dose of orally ingested fucoidan is sufficient to affect the expression of genes related to immunity, inflammation, cancer, and neurological function. A placebo-controlled double-blind study was performed in nine healthy, male volunteers (age 25–65 years-old).…”
Section: Discussionmentioning
confidence: 99%